Nil tremendum ou les stratégies de conjurer la peur ancestrale dans les Lumières françaises. Jan Potocki et ses antécédents - Zatorska, Izabella (Romanica Silesiana)
Enlighted elites were imperatively struggling against fear, perceived as the source of tensions and social conflicts. This struggle incited a number of very different initiatives, such as the articles from Encyclopédie [Encyclopaedia] by Diderot / d’Alembert or from Dictionnaire philosophique [Philosophical Dictionary] by Voltaire, philosophical tales by the latter and, finally, the philosophical novel by Jan Potocki, in its two versions from 1804 and 1810, recently discovered by François Rosset and Dominique Triaire. The fear of supernatural and, especially, of death is being tamed thanks to well-known literary proceedings (irony or the comic), which may be described using the theory of games by Roger Caillois or by Colas Duflo. Hereafter, we are putting forward the ambivalence appearing in the first case and particularly noticeable in Potocki’s writings. Key words: Voltaire, Jan Potocki, philosophical tale, philosophical novel, theory of games, fear, irony, the comic